Kinds of Meaning in Classical Arabic from More Recent Denotational Theory Perspectives - Al-Heeh, Sami (e-Journal of Linguistics, 2021)
This paper explores the extent to which meaning is conveyed in Classical Arabic. It aims to quantify as well as qualify the various kinds of meaning and the techniques used to advance them on the linguistic various levels. From a semantic perspective, it first categorizes kinds of meaning according to denotation and connotations satisfied by paraphrasing and definition and to 'sense' perceived by ostensive, i.e. sensory, definition. Second, it examines the syntactic meaning achieved by composition, addition, and (inclusively but exceptionally by) Arabic sentence-pattern switching and phoneme clipping on the structural level. Then, it advances lexical meaning expressed by synonyms, antonyms, hyponyms, meronyms, polysemous words, and family resemblances. Finally, it presents the categorematic word that can carry full meaning and the syncategorematic one which can only modify meaning. In both types, morphemes are isolated and allomorphs are exemplified. The paper quotes from the Holy Script of Islam, the Noble Quran, for its linguistic preciseness and conciseness.